Analisis ANALISIS SISA BESI TULANGAN MENGGUNAKAN SOFTWARE CUTTING OPTIMIZATION PRO PADA KONSTRUKSI GEDUNG - I Gusti Ngurah Eka Partama; I Gusti Made Sudika; Ega Louis Bagus Saputra (Fakultas Sains dan Teknologi Universitas Ngurah Rai, 2023)
Making a bar bending schedule is one of the efforts to control the waste material of reinforcing steel, but in calculating the waste material manually it is still not optimal. In order to reduce the waste material, it is attempted to use software namely Cutting Optimization Pro (SCOP) which produces the output in the form of the most optimal pattern of cutting of reinforcing steel. The research object for the Villa Stilo Development Project was chosen because in the concrete structure work process there was quite a lot of steel material left over. The purpose of this study is to determine the needs and total costs, the percentage of waste and the waste cost of steel reinforcement. The method used is descriptive analytic, with the data used in the form of working drawings and budget plans. The need for steel is calculated using Bar Bending Schedule (BBS) method, for the waste of the material is analyzed using manual calculations (conventional) and compared using SCOP. The results of the analysis showed that the need for reinforcing steel in the Villa Stilo Development Project was 1,205 rods of Ø8 steel, 103 rods of Ø10 steel, 75 rods of D10 steel, 882 rods of D13 steel, 21 sheets of M7 wiremesh and 18 sheets of M10 wiremesh. With a total cost of steel needs of Rp. 225,937,460.00. The percentage of waste generated by using the conventional method is 9.43%, while using SCOP is 4.36%. For waste costs using the conventional method of Rp. 19,937,700, while using SCOP of Rp. 9,693,760.00 or the waste cost using the conventional method is 105.68% bigger than using SCOP.